An evaluation of the application of the circular production model in agriculture: case study of Nyanza district, Rwanda - Sangwa, Sixbert; Keza, Larissa Diane; Uwumuremyi, Delphine; Nijman-Ross, Elke (Frontiers in Sustainability, 2023)
This research explored the status of the application of circular economy (CE) principles in the agricultural sector in the Nyanza district of Rwanda, A multi-methodological approach was used to collect mixed data from farmers and key stakeholders operating in two selected sectors of Muyira and Busasamana to evaluate the solid waste management value chain, assess the adoption of ecological latrines and explore farmers' perception on human waste fertilizers as a CE principle. Quantitative data was collected through interviews with a sample of 1244 farmers randomly selected from Busasamana (n=598) and Muyira (n=646). The data were interpreted according to the research questions and analysis was done using descriptive and inferential statistics. The results indicated that waste management is still at a rudimentary stage in the localities studied, with a waste sorting rate of 2.2% and 1.1% but with a willingness of 96.9% in Busasamana and 99.5% in Muyira sector to sort waste from organic to non-organic at source. The majority of participants, represented by 80.3% of the surveyed farming households in Busasamana and 97.5% of their counterparts in Muyira generate between 1-2 sacks of household waste per week. Food-related waste was the most predominant in Busasamana households, accounting for 99.5% while Muyira farmer households generate both food and yard wastes in proportions of 58% and 41.6 % respectively. It’s worth knowing that waste is dumped in the domestic rubbish pits in the two sectors, with 88% and 77.9%in Busasamana and Muyira sectors. Furthermore, the research revealed the absence of a waste collection and transport provider and a landfill in the Muyira sector, while waste collection facilities are available in Busasamana. Low adoption rates of eco-friendly latrines were observed, as farmers trick to the use of traditional pit latrines at 98.2% of the households in Busasamana and 100% in Muyira sector. Muyira being far ahead of its Busasamana counterparts in toilet dislodging (67% vs. 33%). Greater involvement of all actors in the system to ensure the success of the application of CE practices and initiatives was recommended as well as awareness raising and capacity building on the use of ecological latrines.